(untitled) (Journal of the College of Education for Women, 2019)
This study aims at exploring primary school pupils’ understanding ofthe meaning of lexical items and language structures. The study sampleconsists of 40 second year primary school pupils. The results reveal thatthe percentage of the pupils’. Understanding of the meaning of lexical itemsis 72.7% that of language structures "verbal and nominal clauses" is 82.3%and that of language structures "negative, interrogative, vocative, referenceand prepositions" is 86.5%. The study also reveals that there is nostatistically significant difference between the achievement of male pupilsand that of females.